Redefining Epistemology: Exploring a New Paradigma in Islamic Education Research - Fauji, Ikang; Nugraha, Mulyawan Safwandy (Universitas Pendidikan Indonesia (UPI), 2024)
This study showed epistemological renewal that integrates the values of the Qur'an and As-Sunnah as the main foundation. The Epistemology of Islamic education pays attention to cognition as well as the development of spirituality and the character of students. This is very important because the goal of Islamic education is to produce students who not only have cognitive intelligence but also have high moral and social awareness. The spread of a more materialistic and secular Western educational paradigm is a major problem. Therefore, this study investigated new methods in the epistemology of Islamic education, including empirical, scientific, philosophical, and religious methods. This method created a broader and integrative education system that can produce the ideal human being (insān Kamil), which is in line with the goals of Islamic education.